Pinzamiento del cordón umbilical precoz al nacer y anemia en lactantes a los 6 meses de edad - Benites Suarez, Jessica Diana (2019)
Introduction: Childhood anemia is a public health problem, in Peru it is more prevalent between 6 and 18 months of age, it is also related to child malnutrition. Objective: To analyze the association between early cord clamping at birth and anemia in infants at 6 months of age. Materials and methods: A retrospective case-control analytical observational study, 180 infants of 6 months of age attended in January - October 2018 in Healthy Child Growth and Development - Pediatrics of the Regional Teaching Hospital of Trujillo (60 cases and 120 controls).. A Chi- square for qualitative variables and the risk estimate with Odds ratio at a 95% CI. Results: At 6 months of age, infants showed a statistically significant difference in hemoglobin concentration between the early and delayed cord clamping groups (OR of 18.38 and p < 0.01). Conclusions: There is an association between clamping early cord at birth and anemia at 6 months. Being the early cord clamping risk factor for anemia.